A cinematic book: the Maias on the cinema screen - Sobral, Filomena Antunes (2019)
The Maias - Scenes from Romantic Life - 2014 is a Portuguese film directed by João Botelho that confirms the dramatic qualities widely recognized to Eça de Queiroz’s nineteenth century novel - The Maias (1888). Surprisingly, only in 2014 was the cinematic approach conceived by proposing a unique and empathic creative dialogue with the novel. Thus, the objective of this paper is to establish a frame of reference which guides the reading to an interpretative proposal of João Botelho’s filmic adaptation. The text emphasizes the transformational grammar of the adaptation in the composition of an artful and operatic-theatrical ingenious film.